Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s11695-014-1447-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race and Socioeconomic Status with Outcomes Following Laparoscopic Roux-en-Y Gastric Bypass

Abstract: Although African Americans had a statistically significant lower %EWL, %WL, and ΔBMI, both groups had durable weight loss and comparable rates of improvement or remission of obesity-associated comorbidities. Thus, both groups have significant improvement in their overall health after LRYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 43 publications
1
5
0
1
Order By: Relevance
“…This is an important finding, as prior studies have not identified such statistically and clinically significant variations by race in the resolution of hypertension after LRYGB. 13,17,18,22 Consistent with the known increased prevalence of hypertension in the general African-American population, Adams observed the highest rates of hypertension in Asians and African-Americans among morbidly obese patients pre-operative for LRYGB. 1 The results here indicate that the increased African-American propensity for hypertension extends to impaired high blood pressure resolution following LRYGB.…”
Section: Discussionmentioning
confidence: 84%
“…This is an important finding, as prior studies have not identified such statistically and clinically significant variations by race in the resolution of hypertension after LRYGB. 13,17,18,22 Consistent with the known increased prevalence of hypertension in the general African-American population, Adams observed the highest rates of hypertension in Asians and African-Americans among morbidly obese patients pre-operative for LRYGB. 1 The results here indicate that the increased African-American propensity for hypertension extends to impaired high blood pressure resolution following LRYGB.…”
Section: Discussionmentioning
confidence: 84%
“…This suggests that race/ethnicity driven metabolic risk may explain attenuated responses to surgery [3236]. Although not the purpose of the present review, it is important to consider that psychosocial factors including but not limited to eating behavior, eating disorders, mental illness, substance abuse, and socioeconomic status may also contribute to bariatric surgery resistance [3740]. In summary, targeting metabolically modifiable risk factors with lifestyle medicine in high-risk populations may be beneficial for bariatric surgery resistant patients.…”
Section: Bariatric Surgery Resistancementioning
confidence: 99%
“…The majority but not all studies report that after laparoscopic Roux-en-Y gastric bypass, NH black subjects achieve smaller percent weight loss, percent excess weight loss and change in BMI than NH white subjects [106][107][108][109][110]. Of even greater importance are changes in co-existing diseases, but the data are so far conflicting: one study showed comparable remission or improvement in obesity-associated comorbidities after gastric bypass [108], while another found that the metabolic syndrome is less likely to resolve in NH black patients [111].…”
Section: Response To Weight Loss Treatmentsmentioning
confidence: 99%
“…Of even greater importance are changes in co-existing diseases, but the data are so far conflicting: one study showed comparable remission or improvement in obesity-associated comorbidities after gastric bypass [108], while another found that the metabolic syndrome is less likely to resolve in NH black patients [111].…”
Section: Response To Weight Loss Treatmentsmentioning
confidence: 99%